Silybin has therapeutic efficacy against non-small cell lung cancer through targeting of Skp2 - Shi-Bing Zhang; Ming Hong; Xiao-Yang Sun; Da Huang; Dan-Hua He; Yu-Fei Chen; Yong Yuan; Yong-Qiang Liu (Compuscript Ltd, 2022)
Silybin (SB), a natural flavonoid isolated from Silybum marianum, has been used to treat hepatic fibrosis in clinical settings and as a dietary supplement, because of its hepatoprotective potential. Numerous studies have shown that SB also exerts promising anticancer effects; however, the anticancer targets of SB and the underlying mechanism were unclear. Herein, we found that SB significantly inhibited the proliferation of non-small cell lung cancer without causing cytotoxicity toward normal Beas-2B bronchial epithelial cells. Mechanistically, SB binds the F-box protein Skp2 and disrupts Skp1-Skp2 interaction, thereby decreasing Skp2 protein levels, inducing accumulation of Skp2 substrates, and leading to G1-phase cell-cycle arrest and the suppression of cell migration. In lung orthotopic xenografts, SB also significantly decreased Skp2 expression and increased p27/Kip1 protein levels. SB administration inhibited tumor growth and metastasis in lung tissue, thus prolonging survival time in mice without causing obvious toxicity. Thus, SB is a potential Skp2-targeting agent that warrants further clinical investigation.